Feminine identity and vocational-occupational role - Semidober, Isabel (2002)
This essay is based on an investigation carried out while serving an apprenticeship for teachers, during the Women Study Seminar, at Cadiz University, Spain, in 1997. It could be made due to a fellowship granted by Kennedy University of Argentine Republic headed, at that time, by Dra. Inmaculada Díaz Narbona. It contains cases related to Vocational and Occupational Orientation, collected by myself and by colleagues who were supervised, and pertaining to the private as well as to the institutional ambit in Argentina. Whenever we become aware of the changes occurred all over the world in relation to study and work possibilities, especially in the West, we wonder whether the consulting women have real choice opportunities regarding their life project. This investigation was intended to find out the variables which influence the "adjustment" or "conflict" of the feminine identity and the occupational role of young women studying at university.